2003
DOI: 10.1590/s1677-55382003000200008
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous epididymal sperm aspiration (PESA) in men with obstructive azoospermia

Abstract: Objectives: Assessing the efficiency of repeated percutaneous epididymal sperm aspiration (PESA) in men with obstructive azoospermia, and also the possibility of cryopreservation of remaining material for future use in intracytoplasmic sperm injection (ICSI).Method: Retrospective study, in which 79 procedures of PESA were assessed in 58 patients (mean age = 45 years), whose partners had mean age of 34 years. Vasectomy was the most frequent cause of obstructive azoospermia (n = 46).Results: Motile spermatozoa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…The use of intracytoplasmic sperm injection (ICSI) in clinical practice revolutionized the treatment of patients with severe male factor of infertility [Palermo et al 1993;Devroey et al 1995;Glina et al 2003]. While initially this type of treatment was limited to patients with obstructive azoospermia [Craft et al 1997;Schoysman et al 1993], later studies reported the successful recovery of mature sperm in patients with non-obstructive azoospermia [Devroey et al 1995] leading to the first successful pregnancies and deliveries in this later group of infertile patients [Tournaye et al 1995;Lewin et al 1996].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of intracytoplasmic sperm injection (ICSI) in clinical practice revolutionized the treatment of patients with severe male factor of infertility [Palermo et al 1993;Devroey et al 1995;Glina et al 2003]. While initially this type of treatment was limited to patients with obstructive azoospermia [Craft et al 1997;Schoysman et al 1993], later studies reported the successful recovery of mature sperm in patients with non-obstructive azoospermia [Devroey et al 1995] leading to the first successful pregnancies and deliveries in this later group of infertile patients [Tournaye et al 1995;Lewin et al 1996].…”
Section: Introductionmentioning
confidence: 99%
“…These procedures can cause physiological consequences leading to several side effects, such as inflammation and haematomas [Schlegel and Su 1997;Ramasamy et al 2005], progressive and irreversible damage to the architecture of the tubules, fibrotic changes [Shufaro et al 2002], testicular atrophy and impaired Leydig cell function [Tash and Schlegel 2001;Bouloux et al 2002;Schill et al 2003]. The pathological changes increased when the procedure was repeated on the same subject [Glina et al 2003]. Surprisingly, published reports indicate that there is lack of consensus to recommend any particular sperm retrieval technique [Van Peperstraten et al 2006;Donoso et al 2007;Rupin 2011;Esteves et al 2011].…”
Section: Introductionmentioning
confidence: 99%
“…5 The literature is rich in studies of the outcomes of sperm acquisition and ICSI. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Nevertheless, few groups have reported SR outcomes in men with OA according to obstruction etiology. 13,14,16 -18 This is important to determine because it will help infertility physicians counsel such patients on the chances of SR and ICSI.…”
mentioning
confidence: 99%
“…Successful repeated PESA was performed up to three times, with recovery of motile sperm in over 80% of the cases. Forty-three percent of PESA procedures yielded sufficient spermatozoa to allow cryopreservation (42). Esteves et al reported a SRR of 97.9% among 142 men with OA.…”
Section: Impact Of the Methods Of Collection On Retrieval Success And mentioning
confidence: 99%